SISTEM INFORMASI PEMASARAN PRODUK UMKM BERBASIS WEBSITE - Nungsiyati, Nungsiyati; Febriyani, Eva; Mukodimah, Siti; Muslihudin, Muhamad (Jurnal TAM (Technology Acceptance Model), 2024)
This research was conducted to design a marketing information system for Micro, Small and Medium Enterprises (MSMEs). because MSMEs in Payung Batu Village face various problems in developing their business, especially in terms of product marketing. This is due to the lack of effective use of marketing information systems by MSMEs in the village. Therefore, research is needed to examine the use of marketing information systems by MSMEs in Payung Batu Village. In research this system uses a qualitative analysis method that can be used to produce a more comprehensive study of a phenomenon. Data collection in this research system method uses the waterfall method system development method. Because by using this method MSMEs data can have a series of clear and structured system workflows. The results of this study are the application of a web-based system to the MSMEs product marketing information system in Payung Batu Village to increase marketing and sales reach. This research shows that the use of marketing information systems can help improve MSMEs performance and innovation, as well as influence buyer behavior and brand loyalty.